Hubungan Tingkat Kecemasan Dengan Kualitas Tidur Pasien Kanker Di RSKB Columbia Asia Semarang - Yushita Septiana; Dwi Retnaningsih (Journal of Health, Medical, and Psychological Studies, 2026)
This study aimed to examine the relationship between anxiety levels and sleep quality among cancer patients in a clinical setting. A quantitative empirical approach with a cross-sectional design was employed, involving 35 respondents selected through consecutive sampling. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS), while sleep quality was assessed using the Athens Insomnia Scale (AIS). The findings revealed that most patients experienced moderate to severe anxiety and mild to moderate insomnia. Bivariate analysis using Spearman Rank correlation demonstrated a very strong and statistically significant positive relationship between anxiety levels and sleep quality (ρ = 0.937; p < 0.05). Higher anxiety levels were consistently associated with poorer sleep quality. This relationship can be explained through biopsychosocial mechanisms, including sympathetic nervous system activation and stress-related hormonal changes that disrupt sleep regulation. These findings highlight the importance of integrating psychological assessment and sleep evaluation into routine cancer care. Comprehensive interventions, including psychosocial support, patient education, and relaxation techniques, are recommended to improve overall patient well-being and clinical outcomes.